Study of the Mechanisms Involved in the Adsorption of Amitriptyline from Aqueous Solution onto Activated Carbons - B. Ledesma; S. Román; J.F. González; F. Zamora; M.C. Rayo (Adsorption Science & Technology)
Two commercial activated carbons (DA and CB) differing in their porosity (one being microporous and the other mesoporous) and in their surface chemistries (one being acidic and the other basic in character) were modified by thermal and oxidizing treatment in order to change their surface properties. The changes induced by these processes were studied by means of ultimate analyses, nitrogen adsorption isotherms measured at −196 °C, mercury porosimetry, FT-IR spectroscopy and determination of their point of zero charge (PZC) values. Subsequently, the adsorption of amitriptyline onto both the pristine and treated carbons was studied at pH values of 3 and 7 and a temperature of 25 °C. The results obtained allowed the possible mechanisms governing the adsorption process to be analyzed in order to optimize the type of adsorbent needed to remove this particular drug from aqueous solution.